Bio-Economic Analysis of Red Snapper (Lutjanus spp.) in The Waters of Makassar City, South Sulawesi, Indonesia - Yusuf, Muhammad; Riana, Andi Dyna; Rusneni, Rusneni; Malik, Malik; Ibrahim, Mardiana; Emakarim, Lompo Ramos; Umar, Nur Asia; Tajuddin, Mustamin; Hajriani, Sri (Faculty of Fisheries and Marine Science, Brawijaya University, 2024)
Effective fishery management is essential for sustaining fish resources, economic growth, and social well-being. Achieving optimal and sustainable exploitation levels requires determining key metrics: biomass, optimal effort, catch, and costs under various management regimes (sole owner/open access, MSY, MEY, and dynamic). This study aims to determine the optimal and sustainable management level of red snappers (Lutjanus spp.) in the waters of Makassar City. This research uses a quantitative analysis method with a bio-economic analysis technique. The research was conducted in the waters of Makassar City from June to December 2022. The bio-economic analysis indicates that red snapper production in Makassar waters can be further optimized, but current fishing efforts exceed the optimal limit, requiring improvements in the catch effectiveness and efficiency of the catch. The high fishing effort for red snapper in this area indicates inefficient fishing activities, which suggest the potential for fishing optimization. To reach the Maximum Sustainable Yield (MSY), the current fishing effort, which has reached 163,496 trips, must be reduced by 78,902 trips, or around 48.26%, to reach the optimal fishing point. Similarly, to achieve The Maximum Economic Yield (MEY), the fishing effort must be reduced by 90,925 trips, or approximately 55.61%.